Institutional change and endogenous development: Theoretical contributions - Bruna Coradini Nader Adam; Jo\~ao Garibaldi Almeida Viana; Carine Dalla Valle (Economies, 2025)
This essay aims to address the existing theoretical gap regarding the in-depth study of institutional change and its relationship with the endogenous development potential of regions. The intersection of these two theoretical approaches offers an understanding of how changes in formal and informal institutions can influence local development, especially when internal resources and local capacities drive this progress. The research was conducted using a bibliographic method and adopts a qualitative approach, seeking an in-depth understanding of the topic. Relevant assumptions about endogenous development were presented and articulated with the institutional change by Douglass North. The contribution of this theoretical approach was to highlight the role of institutional change as a driving force behind regional endogenous development, defining, from the perspective of endogenous development, the institutions that are determinants of the development process of economies. Based on our theoretical construction, we suggest future studies that are concerned with illustrating empirical cases of how formal and informal institutions can promote endogenous development.
Keywords: 330; economic development; institutions; institutional economics; regional development